(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Comparison of production management using the EFQM Excellence Model. Purpose: The aim of the research is based on a comparison of production management using the EFQM Excellence Model, to establish identity and difference. The aim is to improve the management of production and by using the model closer to excellence. Method: An identification method of benchmarking. Results: The results show tolerance, which represent an opportunity to improve production management with excellence. Organization: If we take into account the results of the organization, this would be an asset to the organization. Society: Method comparisons can also be used in the wider environment. Originality: The survey is unique and the first of its kind in the manufacturing organization. Limitations/Future Research: With this research we will gain improvements in production management through design excellence.